Emigration from Within*. Issue 4 (December 2016) - Szekacs-Weisz, Judit
Abstract Listening to the stories of people belonging to different generations in motion—both in our consulting rooms and our personal lives—served as introductory lectures into the fundamental aspects of changing context. Through these rich and diverse stories, one enters a territory which is not only multilingual but multidimensional: defined and shaped by historical, political, economic and socio-cultural transformations. Giving voice to these silent stories proved helpful for us when going behind walls that traditional analysis could not always penetrate, partly because, in many cases, analysts and analysands have been struggling with the same untouchable issues. It is our professional task to find creative ways to make sense of past and recent experiences of emigration, new prejudices, discriminative forms and attitudes—in order to achieve a better psychoanalytical understanding of the external and internal confusion that has been brought about by the immense changes during the past centuries and the present one.